Controlling time and shaping the self : developments in autobiographical writing since the sixteenth century - Baggerman, Arianne; Dekker, Rudolf; Mascuch, Michael (Egodocuments and history series ;, 2011)
This book explores new questions and approaches to the rise of autobiographical writing since the early modern period. What motivated more and more men and women to write records of their private life? How could private writing grow into a bestselling genre? How was this rapidly expanding genre influenced by new ideas about history that emerged around 1800? How do we explain the paradox of the apparent privacy of publicity in many autobiographies? Such questions are addressed with reference to well-known autobiographies and an abundance of newfound works by persons hitherto unknown, not only.